2015
DOI: 10.1111/jre.12278
|View full text |Cite
|
Sign up to set email alerts
|

Full mouth periodontal debridement with or without adjunctive metronidazole gel in smoking patients with chronic periodontitis: A pilot study

Abstract: Adjunctive use of Mtz (gel or tablet) to periodontal debridement had similar clinical and microbiological improvement compared to treatment with placebo + periodontal debridement in smokers with chronic periodontitis up to 6 mo post-treatment. Further studies are necessary to confirm the clinical relevance of these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…That study determined that treatment with minocycline microspheres and metronidazole gel improved PPD and CAL in patients with periodontitis compared to SRP alone (44). Bergamaschi et al compared the effect of metronidazole (local and systemic) as adjunctive therapy to full mouth periodontal debridement in smokers with chronic periodontitis, and concluded that adjunctive use of metronidazole (gel or tablet) to periodontal debridement led to similar clinical and microbiological improvement compared to treatment with placebo + periodontal debridement in smokers with chronic periodontitis up to 6 months after treatment (45). Singh et al conducted a study to comparatively evaluate the efficacy of local delivery of Aloe vera and metronidazole, as an adjunctive therapy to SRP in chronic periodontitis patients.…”
Section: Discussionmentioning
confidence: 99%
“…That study determined that treatment with minocycline microspheres and metronidazole gel improved PPD and CAL in patients with periodontitis compared to SRP alone (44). Bergamaschi et al compared the effect of metronidazole (local and systemic) as adjunctive therapy to full mouth periodontal debridement in smokers with chronic periodontitis, and concluded that adjunctive use of metronidazole (gel or tablet) to periodontal debridement led to similar clinical and microbiological improvement compared to treatment with placebo + periodontal debridement in smokers with chronic periodontitis up to 6 months after treatment (45). Singh et al conducted a study to comparatively evaluate the efficacy of local delivery of Aloe vera and metronidazole, as an adjunctive therapy to SRP in chronic periodontitis patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, PPD levels did not differ signi cantly between the three groups at the beginning of treatment and after three months; In other words, all treatments were equally effective, and no signi cant difference was seen (p > 0.05). Similar to the present study, Bergamaschi et al [14] conducted a pilot clinical trial in Brazil in 2015 to compare the effect of local metronidazole gel or systemic tablet use as adjunctive therapy in line with complete oral debridement in smoker patients with chronic periodontitis. PPD improved in all groups from the rst month to the last evaluation time (P < 0.05).…”
Section: Discussionmentioning
confidence: 83%
“…In a study conducted by Dua et al, 34 a combination of metronidazole and norfloxacin applied topically was found to be safe and effective enough to be used as an alternative treatment in local bacterial infection and burn wound healing. Bergamaschi et al, 35 in a study of patients with chronic periodontitis and periodontal debridement, reported that topical and systemic administration of metronidazole produced the same results as the untreated control group. Kadkhoda et al, 36 in a study of patients with aggressive periodontitis and periodontal debridement who received a topical application of metronidazole, found that only periodontal debridement was significantly reduced.…”
Section: Discussionmentioning
confidence: 92%